Pengaruh Pelatihan, Disiplin Kerja & Gaya Kepemimpinan terhadap Produktivitas Kerja Karyawan Pada PT Federal Nittan Industries - nurlaela eva puji lestari (Universitas Bina Sarana Informatika, 2018)
Employees are social beings who become the main wealth for every company. They become planners, executors and controllers who always play an active role in realizing the company's goals. Every Company wants its employees to excel and work effectively. Thus need to be given training, applied work discipline, and supported by a good leadership style to increase employee work productivity.The sample used for data collection in this study amounted to 134 employees of PT . Likert scale used by writer to change qualitative data in questionnaire become quantitative data. The purpose of this study is to determine and analyze the magnitude of the influence of Training (X1), work discipline (X2), leadership style (X3) to labor productivity (Y) of PT. Federal Nittan Industries. The calculation of the questionnaire results using a simple linear regression formula. All of the author's calculations were assisted by the SPSS version 20 program released by IBM. Based on the analysis and data processing according to the calculation of correlation coefficient can be seen that the Motivation of Performance has a very strong relationship that is equal to 0.961 and according to the calculation of the coefficient of determination, can be known quite large is 92.3%, then influence Motivation on Performance can be seen through simple linear regression that is Y = 2,670 + 0,901X.